2013
DOI: 10.1002/ps.3538
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterisation of NADPH-dependent cytochrome P450 reductase gene in the cotton bollworm,Helicoverpa armigera

Abstract: The results indicate that HaCPR is important for the development of H. armigera and may play an essential role in the P450-mediated insecticide resistance of H. armigera to fenvalerate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…The conserved polyadenylation signal (AATAAA) nucleotide sequence of SeCPR is consistent with most other CPRs in eukaryotes ( Guo and Sherman 1996 ; Zhao et al. 2014 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The conserved polyadenylation signal (AATAAA) nucleotide sequence of SeCPR is consistent with most other CPRs in eukaryotes ( Guo and Sherman 1996 ; Zhao et al. 2014 ).…”
Section: Discussionsupporting
confidence: 73%
“…Similar to the conserved motif in other organisms ( Ingelman et al. 1997 ; Zhao et al. 2014 ), the FAD-binding motif of Se CPR consists of three amino acids, Arg 467, Tyr 469, and Ser 470 as well.…”
Section: Resultsmentioning
confidence: 87%
“…Several studies have shown that CPRs were inducible by drugs in other organisms. For instance, the level of CPR mRNA in Helicoverpa armigera was up-regulated in the midgut of 6th instar larvae after treated with phenobarbital (PB) in the diet 42 . Shephard et al 43 reported that the activity of the CPR enzyme in rat liver microsomal membranes increased to 2.7- fold after PB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gossypol-induced P450s exhibited high divergence and at least five of them ( CYP321A1 , CYP9A12 , CYP9A14 , CYP6AE11 and CYP6B7 ) contributed to cotton bollworm ( Helicoverpa armigera ) tolerance of deltamethrin [ 26 ]. Five genes, CYP337B1 , CYP9A12 , CYP9A14 , CYP6AE11 and CYP6B7 showed considerably high expression in the resistant strain of Helicoverpa armigera against fenvalerate pesticide [ 27 , 28 ]. The CYP9A14 and CYP6AE11 were significantly over-expressed in Helicoverpa armigera strains from Burkina Faso and Spain when compared with Heliar, a susceptible strain [ 29 ].…”
Section: Introductionmentioning
confidence: 99%